The Influence of Promotion Mix, Brand Image and Lifestyle on Purchase Decisions at Tokopedia with Consumer Behavior as An Intervening Variable - Saputra, Prastya Harys; Alimudin, Arasy; Suyono, Joko (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
The purpose of this research is to determine and analyze the influence of Promotion mix on Consumer Behavior, Brand image on Consumer Behavior, Lifestyle on Consumer Behavior, Promotion mix on Purchase Decisions, Brand image on Purchase Decisions, Lifestyle on Purchase Decisions, Consumer Behavior on Purchase Decisions , Promotion mix on purchase decisions with consumer behavior as an intervening variable, brand image on purchase decisions with consumer behavior as an intervening variable, lifestyle on purchase decisions with consumer behavior as an intervening variable on Tokopedia. The data collection technique used to fill out a questionnaire using the Purposive Sampling method which was distributed to the sample population of 100 respondents and processed using the SEM-PLS application. And the research results show that there is a significant influence of Promotion mix on Consumer Behavior, there is a significant influence of Brand image on Consumer Behavior, there is a significant influence of Lifestyle on Consumer Behavior, there is a significant influence of Promotion mix on Purchase Decisions, there is a significant influence of Brand image on Purchase Decisions , there is a significant influence of Lifestyle on Purchase Decisions, there is a significant influence of Consumer Behavior on Purchase Decisions, there is a significant influence of Promotion mix on Purchase Decisions with Consumer Behavior as an intervening variable, in this research it is known that there is no significant influence of Brand image on Purchase Decisions with Consumer Behavior as an intervening variable, there is a significant influence of lifestyle on purchase decisions with consumer behavior as an intervening variable in Tokopedia.